Attachment and temperament revisited: infant distress, attachment disorganisation and the serotonin transporter polymorphism. (1st January 2016) - Brumariu, Laura E.; Bureau, Jean-François; Nemoda, Zsofia; Sasvari-Szekely, Maria; Lyons-Ruth, Karlen
Abstract: Objective: This study's aim was to evaluate whether infant disorganised attachment and infant proneness to distress exhibited differential relations to infant genetic factors as indexed by the serotonin transporter polymorphism.Background: The role of the short allele of the serotonin transporter polymorphism (5-HTTLPR) in enhancing sensitivity to fearful and negative affect has been well-established. In the current study, we used this known property of the short allele to provide a test of an important postulate of attachment theory, namely that infant attachment security or disorganisation is not a function of the infant's proneness to distress.Methods: Participants were 39 parents and infants assessed between 12 and 18 months in the Strange Situation Procedure. Genotype categories for the 5-HTTLPR (and rs25531) were created by both the original and the reclassified grouping system; infant proneness to distress was assessed directly in the Strange Situation Procedure. We also assessed maternal behaviour at 18 months to evaluate whether any observed genetic effect indicated a passive effect through the mother.Results: Consistent with previous findings, the 5-HTTLPR short allele was significantly related to the infant's wariness and distress, but was not related to attachment security or attachment disorganisation. In addition, maternal disrupted interaction with the infant was not related to infant genotype or infant distress.Conclusion: Results support the concept that infant proneness to distress is associated with serotonergic factors while infant attachment security or disorganisation is not a function of either 5-HTTLPR or behaviourally rated proneness to distress.